Demand For Indonesian Plywood in The South Korean Market - Sherly Syahrones; Bintang Charles Hamonangan Simangunsong; Elisa Ganda Togu Manurung (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Indonesia is a tropical country with abundant forest resources, and plywood is a key value-added product. Among the globally traded plywood products, HS 441231 accounts for the largest share and is a strategic component of Indonesia’s exports. South Korea is one of Indonesia’s main export destinations, as imports largely satisfy its plywood demand. Although Indonesia maintains a dominant position, its exports to South Korea have declined in recent years amid competition from Malaysia and Vietnam. Given the high supplier concentration, understanding South Korea’s import demand structure is increasingly important.Purpose: This study analyzes the demand for Indonesian plywood (HS 441231) in the South Korean market using the LA/AIDS and QUAIDS models to assess price and expenditure responses and evaluate Indonesia’s position relative to major competitors.Design/methodology/approach: The analysis uses monthly South Korean import data for HS 441231 from 2010 to 2024. LA/AIDS and QUAIDS models are estimated using SUR and NLSUR with adding-up, homogeneity, and symmetry restrictions.Findings/Result: Indonesian plywood holds the largest import share, shows elastic demand, and functions as a normal good. The quadratic component of the QUAIDS is significant, indicating a nonlinear consumption pattern. Indonesia has a substitution relationship with Malaysia and a complementary relationship with Vietnam.Conclusion: Indonesia’s competitiveness in the South Korean market is primarily price-based, indicating the need for greater cost efficiency, enhanced quality, and compliance with certification requirements to achieve a more sustainable position.Originality/value (State of the art): This study contributes to the literature by combining LA/AIDS and QUAIDS to analyze South Korea’s plywood demand, providing empirical insights into cross-country substitution dynamics. Keywords: elasticity, expenditure share, import competition, LA/AIDS, QUAIDS